Blockchain Technology: A Review Study on Improving Efficiency and Transparency in Agricultural Supply Chains - Mwewa, Timothy; Lungu, Gilbert; Turyasingura, Benson; Umer, Yusuf; Chavula, Petros (Jurnal Galaksi, 2024)
The agricultural sector is vital to economic development and food security in Sub-Saharan Africa (SSA). However, persistent challenges in agricultural supply chains, such as inefficiencies, lack of transparency, and limited traceability, contribute to high post-harvest losses, unfair pricing for farmers, and reduced consumer trust. Blockchain technology, with its decentralized and transparent ledger system, offers a promising solution to these issues. This review explores blockchain’s potential to improve supply chain efficiency and transparency in SSA. By integrating blockchain with smart contracts, IoT devices, and real-time data sharing, stakeholders can enhance traceability, automate processes, and reduce transaction costs. Blockchain-based platforms provide direct market access for farmers, ensuring fair pricing and minimizing intermediary influence. Furthermore, blockchain’s immutable nature guarantees data credibility, fostering consumer trust and compliance with quality standards. Despite its potential, blockchain adoption in SSA faces challenges, including high costs, inadequate infrastructure, limited technical expertise, and low awareness of its benefits. Addressing these barriers requires affordable, scalable solutions and supportive policy frameworks. This review highlights blockchain’s transformative role in resolving inefficiencies and improving transparency in SSA’s agricultural supply chains. Collaborative efforts among governments, private stakeholders, and international organizations are crucial to fostering adoption, driving economic growth, and enhancing food security.